Effect of fluconazole on the pharmacokinetics of fuzuloparib: an open-label, crossover study in Chinese healthy male volunteers - Chen, Xue; Yang, Feng; Zhao, Jiao; Tang, Qi; Heng, Jianfu; Deng, Jun; Zhang, Jin; Chen, Yong; Li, Kunyan; Wang, Jing (Cancer chemotherapy and pharmacology, 2022)
Purpose Fuzuloparib (AiRuiYi TM , formerly fluzoparib, SHR3162) is a new orally active poly adenosine diphosphate ribose polymerase (PARP) inhibitor. It has multiple pharmacological activities in breast, ovarian, and prostatic cancer. Fuzuloparib is mainly metabolized through the enzyme CYP3A4 may slow fuzuloparib metabolism and increase its concentrations in blood. We evaluated the pharmacokinetics and tolerability of fuzuloparib by fluconazole, which is a broad antifungal agent and a moderate inhibitor of CYP3A4. Methods In this study, the effects of CYP3A4 inhibition on the pharmacokinetics of fuzuloparib were assessed in a total of 20 healthy Chinese male subjects in an open-label, two-period, single-sequence, crossover study. Results Pharmacokinetic parameters, including the maximal plasma concentration ( C max ) , the plasma concentration–time curve from time 0 to last measurable area under concentration (AUC 0−t ), and from time 0 to infinity (AUC 0−∞ ), were increased by 32.4%, 104.5%, and 109.6%, with corresponding 90% confidence intervals of (23–43%), (93–116%), and (98–122%), respectively, when fluconazole was combined with fuzuloparib compared to fuzuloparib alone. There was also a slight increase in the incidence of treatment emergent adverse events, including hyperlipidemia and elevated aspartate transaminase. Conclusion The fuzuloparib is 150 mg b.i.d in clinics use. Our results suggest that fuzuloparib could well be tolerated when administered as a single 20 mg oral dose alone or co-administered with 400 mg fluconazole in healthy male subjects. It is recommended to avoid using moderate CYP3A4 inhibitors together with fuzuloparib or instead of 50 mg when necessary.